A wake-up call: Covid-19 and its impact on reforming biosciences education towards resiliency and sustainability - Cheema, Manraj Singh; Syed Alwi, Sharifah Sakinah; Md Hashim, Nur Fariesha; Othman, Zulkefley; Sarchio, Seri Narti Edayu; Liew, Chin Teng; Praveena, Sarva Mangala (UPM Press, 2022)
COVID-19’s global pandemic has had a significant impact on bioscience education, which has switched to online learning. Every entity within the higher education ecosystem, whether technical, pedagogical, or social, has faced a number of challenges as a result of this. Regardless, biosciences education stakeholders have been fast to implement innovative strategies to maintain high standards and quality of biosciences online teaching and learning. This paper focuses on the biosciences education transition toward developing resiliency, as well as the technology resources and approaches that have been deployed in the current context to change biosciences education to be robust in the face of the COVID-19 upheaval. Finally, significant insights into ‘resilience sustainability’ approaches that may be employed in relation to the digitisation of biosciences education in a concerted effort to promote resiliency, adaptability and sustainability in biosciences education are presented